2019
DOI: 10.1093/nar/gkz718
|View full text |Cite
|
Sign up to set email alerts
|

Ularcirc: visualization and enhanced analysis of circular RNAs via back and canonical forward splicing

Abstract: Circular RNAs (circRNA) are a unique class of transcripts that can only be identified from sequence alignments spanning discordant junctions, commonly referred to as backsplice junctions (BSJ). Canonical splicing is also linked with circRNA biogenesis either from the parental transcript or internal to the circRNA, and is not fully utilized in circRNA software. Here we present Ularcirc, a software tool that integrates the visualization of both BSJ and forward splicing junctions and provides downstream analysis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 53 publications
0
14
0
1
Order By: Relevance
“…Of the 8 upregulated circRNAs ( Figure 1(a )), we elected to focus on the novel circRNA hsa_circ_0007364 (hsa_circRNA_100141), which is generated from exon2 and exon3 of PTP4A2 gene through back-splicing ( Figure 1(b )). Further analysis revealed that hsa_circ_0007364 reverse-transcribed using Oligo dT primers was less than from random primers ( Figure 1(c )) [ 22 ], hsa_circ_0007364 is more resistant to RNase R digestion relative to linear PTP4A2 mRNA ( Figure 1(d )), and hsa_circ_0007364 is markedly more stable than PTP4A2 mRNA following transcription inhibition with actinomycin D ( Figure 1(e )).
Figure 1.
…”
Section: Resultsmentioning
confidence: 99%
“…Of the 8 upregulated circRNAs ( Figure 1(a )), we elected to focus on the novel circRNA hsa_circ_0007364 (hsa_circRNA_100141), which is generated from exon2 and exon3 of PTP4A2 gene through back-splicing ( Figure 1(b )). Further analysis revealed that hsa_circ_0007364 reverse-transcribed using Oligo dT primers was less than from random primers ( Figure 1(c )) [ 22 ], hsa_circ_0007364 is more resistant to RNase R digestion relative to linear PTP4A2 mRNA ( Figure 1(d )), and hsa_circ_0007364 is markedly more stable than PTP4A2 mRNA following transcription inhibition with actinomycin D ( Figure 1(e )).
Figure 1.
…”
Section: Resultsmentioning
confidence: 99%
“…This shared nature complicates computational inference, especially for regions within circRNAs far from the BSJs. Indeed, although computational methods to reconstruct full-length circRNAs from short-read RNA-seq data exist [25][26][27][28][29] , these methods are unable to reconstruct long full-length circRNAs 25 . In a recent assessment of state-of-the-art reconstruction strategies, Zheng and colleagues concluded that short-read-based reconstruction methods can only be applied to short circRNAs (200-500 nt, depending on RNA-seq read length) 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, inferring the protein products translated from circRNAs requires full-length circRNA sequences 11 . To fill this gap, several computational methods have been developed to reconstruct full-length circRNAs from short-read RNA-seq data [25][26][27][28][29] . However, these methods are only applicable to short circRNAs (200-500 nt, depending on RNA-seq read length), and are unable to interrogate longer full-length circRNAs 25 .…”
mentioning
confidence: 99%
“…The CRISPR-RfxCas13d system may serve as a useful tool for the discovery and functional study of circRNAs at both the individual and large-scale level in the near future [207]. Finally, an increasing number of online databases have been developed and improved to provide tremendous valuable information, such as Ularcirc [208], IMS-CDA [209], Lnc2Cancer 3.0 [210], LincSNP 3.0 [211], etc. These online resources will be applied for circRNA identification, characterization and functional analyses and serve as tools for investigating the interaction between circRNAs and other molecules (e.g., miRNAs and RBPs).…”
Section: Innovative Approaches For Future Researchmentioning
confidence: 99%